2013
DOI: 10.1108/ajb-08-2012-0048
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of innovations: an overarching framework and research agenda

Abstract: Purpose -The commercialization of innovation, which is key to entrepreneurial success, is a combination of several entrepreneurial activities. Building on research from fields of management, strategy, entrepreneurship, economics, and marketing, the paper summarized the extant literature to develop a framework of commercialization and an agenda for future research. The paper aims to discuss these issues. Design/methodology/approach -Extensive review of literature, which was comprised of 194 articles across 62 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 309 publications
(354 reference statements)
0
31
0
1
Order By: Relevance
“…Studies have found that the first mover could gain a competitive advantage over the late entrant through technology leadership, preemption of assets/raw materials, and buyer switching costs. For example, if the production process for the product requires learning such that the cost of production goes down with cumulative output, a first mover could get cost advantages over the late entrant (Datta et al 2013). First movers could also gain a significant advantage when the technology involved is innovative and can be protected through patents (Lee and Mendelson 2007).…”
Section: Theory Development Andmentioning
confidence: 99%
“…Studies have found that the first mover could gain a competitive advantage over the late entrant through technology leadership, preemption of assets/raw materials, and buyer switching costs. For example, if the production process for the product requires learning such that the cost of production goes down with cumulative output, a first mover could get cost advantages over the late entrant (Datta et al 2013). First movers could also gain a significant advantage when the technology involved is innovative and can be protected through patents (Lee and Mendelson 2007).…”
Section: Theory Development Andmentioning
confidence: 99%
“…Gbadegeshin (2017) indicated that "plan is always a plan" and that plan would change during the spin-off creation process. Commercialization involves six channels of entrepreneurial actions leading to sources of innovations, classification of innovation, market capacity, protection, advancement, and deployment (Datta, Reed & Jessup, 2013). Pellikka and Malinen (2014) showed that business models create operative commercialization process which assists individuals to plan the active delivery system through the research and development process phases.…”
Section: Introductionmentioning
confidence: 99%
“…Also some external factors, including the characteristic regional heterogeneity, caused by the differences in the available resources, economical geographic location, conditions of the scientific and technological sphere and so forth, influences the choice of the business strategy of the enterprises in the competitive environment. Therefore it is necessary to choose the way of commercialization and the completion stage of the project, which are the most suitable for the current situation, considering some factors: type and the field of the use of the innovation, size and possibilities of the enterprise, the purpose and activity, the position in the competitive environment, some other factors [4].…”
Section: Resultsmentioning
confidence: 99%